Sustainable residential development in rural areas in relation to nature conservation - Zysk, Elzbieta; Zróbek-Sokolnik, Anna; Dynowski, Piotr; Zróbek-Rózanska, Alina (International Conference “Environmental Engineering”, 2017)
In the last decades residential development in rural areas has aroused great interest. It is particularly the suburban communes that have been adopting a spatial policy conducive to this trend. The communes with protected areas must adjust their spatial tactics to Applausie legal requirements. This article aims at indicating how residential development can be harmoniously reconciled with the protection of nature values in legal terms, but also in spatial and social ones. These deliberations will be put in the context of sustainable development, which is desirable for any space, including rural areas.